Association of dietary fat intake with skeletal muscle mass and muscle strength in adults aged 20–59: NHANES 2011–2014 - Wang, Shijia; Zhang, Yu; Zhang, Dandan; Wang, Fang; Wei, Wei; Wang, Qiong; Bao, Yuanyuan; Yu, Kang (Frontiers in Nutrition, 2024)
Background Sarcopenia, a progressive loss of skeletal muscle mass and strength, needs to initially prevent in the twenties. Meanwhile, there is a lack of research on the effects of fat consumption on skeletal muscle mass and strength in adults aged 20–59. We aimed to assess associations between dietary fat intake and skeletal muscle mass, as measured by appendicular lean mass adjusted for body mass index (ALMBMI), and muscle strength, as represented by handgrip strength adjusted for body mass index (GSMAXBMI), among adults aged 20–59. Methods Dietary fat intake per kilogram of actual body weight was assessed using two 24h recalls, while ALM and GSMAX were measured using DXA and a handgrip dynamometer, respectively. A weighted multiple linear regression model was employed to analyze the association between dietary fat intake and skeletal muscle mass, utilizing data from the National Health and Nutrition Examination Survey spanning from 2011 to 2014. To assess the non-linear relationship and saturation value between dietary fat intake and skeletal muscle mass, a smooth curve fitting approach and a saturation effect analysis model were utilized. Results The study comprised a total of 5356 subjects. After adjusting for confounding factors, there was a positive association observed between dietary fat intake and ALMBMI as well as GSMAXBMI. The relationship between dietary fat intake and ALMBMI showed an inverted U-shaped curve, as did the association with GSMAXBMI. Turning points were observed at 1.88 g/kg/d for total fat intake and ALMBMI, as well as at 1.64 g/kg/d for total fat intake and GSMAXBMI. Furthermore, turning points were still evident when stratifying by gender, age, protein intake, and physical activity. The turning points were lower in individuals with low protein intake(<0.8 g/kg/d) and high levels of physical activity. Conclusion The moderate dietary fat intake can be beneficial for muscle mass and strength in adults aged 20–59 under specific conditions. Special attention should be directed toward the consumption of fats in individuals with low protein intake and those engaged in high levels of physical activity.